Skagway, Whitehorse and the White Pass and Yukon Route Railway - Clibbon, Peter (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1990)
The White Pass and Yukon Route, a 177 km narrow gauge railway linking the Alaskan coastal port of Skagway with Whitehorse, capital of the Yukon Territory, ceased operations in October, 1982, a casualty of the economic recession of the early 1980s which brought about the collapse of the Territory's hardrock mining industry. The railway had been constructed by British interests between 1898 and 1900, that is, in the aftermath of the Klondike gold rush, and had been in continuous operation since that time. In this paper, the author traces the broad lines of the history of the railway and shows the various ways in which it influenced the development of Skagway and of Whitehorse, its ocean and inland termini respectively. The closing of the railway was a major blow to Skagway, where White Pass Transportation and its subsidiaries were the principal employers, and where over two-thirds of the railway's employees were located. The closing appears to have had a more limited impact on Whitehorse, a much larger community whose economy is now highly diversified.